Chelation by histidine inhibits the vacuolar sequestration of nickel in roots of the hyperaccumulator Thlaspi caerulescens. - Richau, K; Kozhevnikova, A; Seregin, I; Vooijs, R; Koevoets, P; Smith, J; Ivanov, V; Schat, H (2009)
* The mechanisms of enhanced root to shoot metal transport in heavy metal hyperaccumulators are incompletely understood. Here, we compared the distribution of nickel (Ni) over root segments and tissues in the hyperaccumulator Thlaspi caerulescens and the nonhyperaccumulator Thlaspi arvense, and investigated the role of free histidine in Ni xylem loading and Ni transport across the tonoplast. * Nickel accumulation in mature cortical root cells was apparent in T. arvense and in a high-Ni-accumulating T. caerulescens accession, but not in a low-accumulating T. caerulescens accession. * Compared with T. arvense, the concentration of free histidine in T. caerulescens was 10-fold enhanced in roots, but was only slightly higher in leaves, regardless of Ni exposure. Nickel uptake in MgATP-energized root- and shoot-derived tonoplast vesicles was almost completely blocked in T. caerulescens when Ni was supplied as a 1 : 1 Ni-histidine complex, but was uninhibited in T. arvense. Exogenous histidine supply enhanced Ni xylem loading in T. caerulescens but not in T. arvense. * The high rate of root to shoot translocation of Ni in T. caerulescens compared with T. arvense seems to depend on the combination of two distinct characters, that is, a greatly enhanced root histidine concentration and a strongly decreased ability to accumulate histidine-bound Ni in root cell vacuoles.